W Sprawie Definicji Momentu Skupionego Działającego na Ośrodek Sprężysty - Świtka, R. (Engineering Transactions, 1966)
It is demonstrated in the present paper that the effect of action of a single dipole depends on its orientation. It is found that a concentrated moment cannot be identified with a dipole, as is done by some authors. The paper brings a correct definition of a concentrated moment acting in the region of a plane elastic body and on its edge. As an example is obtained the solution of problem of a panel strip with clamped edges, loaded by a concentrated moment.